Laryngeal Mask Airway Insertion in Adult: Comparison between Fully Deflated and Partially Inflated Technique - Uddin, Raihan; Jabbar, Abdul; Muniruzzaman, Muhammad; Khan, MA Salam (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Objective: The laryngeal mask airway (LMA) Is a supraglottic airway device designed to seal aroundthe laryngeal inlet. A controlled study was designed to compare the effectiveness and complications ininserting the LMA when the cuff is fully deflated and partially inflated. Materials and Methods: American society of Anesthesiologists physical status 1 or 2 sixty (60) femalepatients scheduled for gynecologic procedures were included in this study. Patients were randomlyallocated into one of two groups; fully deflated (n=30) and partially inflated group (n=30). A size #4LMA was inserted. The number of attempts, grade of leak and complications were evaluated. Place and duration: The study was performed in BIRDEM General Hospital from January 2018 toDecember 2018. Results: All 60 patients completed the study protocol. The number of attempt, grade of leak andcomplications were not significantly different between the two groups. Conclusion: The fully deflated method Is more accurate and less complications than the partiallyinflated group but which is not significant. JBSA 2019; 32(2): 36-39